PREDIKSI SISA UMUR PAKAI TUBE REFORMER JENIS HP MODIFIED - Nurobiyanto .; Tri Wibowo; Bambang Teguh Prasetyo (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT Tube reformer modified HP type (23Cr-35Ni Nb) is an important component in the fertilizer industry in the primary reformer. Tube reformer is produced in centrifugal casting method that has the hard characteristic, put up with high temperature, pressure and resistance corrosion. It is because it has a large amount of nickel (Ni) and chrome (Cr) elements so that it can hamper the corrosion. The tube reformer has been operated on for 15 years. Based on technical data modified HP tube reformer has 11,4 years of design life and one of the tubes had been burst in beneath, so it needs to decide how long the remaining life assessment of the modified HP reformer tube is. The aim of the research is in order to know how to last long the remaining life assessment of the tube reformer HP modified used, so it can plan to fix/change with a new tube. In order to support the research, it needs some tests such as metallography, hardness test, tensile test, chemical composition, and creep test. According to API 530, to measure how last the remaining life assessment of tube reformer based on creep test which is accelerated by using LMP method can get 52488,35 hours or 5,99 years. The remaining life based on microstructure damage related to the classification diagram of tube wall damage according to L May in C level (or 50 %) is 50,000 hours or 5,77 years. Keywords: Centrifugal casting, tube reformer HP modified, creep test, Larson Miller parameter, remaining life assessment.